Investigation of inner ear drug delivery with a cochlear catheter in piglets as a representative model for human cochlear pharmacokinetics - Yildiz, Erdem; Gadenstaetter, Anselm J.; Gerlitz, Matthias; Landegger, Lukas D.; Liepins, Rudolfs; Nieratschker, Michael; Glueckert, Rudolf; Staecker, Hinrich; Honeder, Clemens; Arnoldner, Christoph (Frontiers in Pharmacology, 2023)
Hearing impairment is the most common sensory disorder in humans, and yet hardly any medications are licensed for the treatment of inner ear pathologies. Intricate pharmacokinetic examinations to better understand drug distribution within this complex organ could facilitate the development of novel therapeutics. For such translational research projects, animal models are indispensable, but differences in inner ear dimensions and other anatomical features complicate the transfer of experimental results to the clinic. The gap between rodents and humans may be bridged using larger animal models such as non-human primates. However, their use is challenging and impeded by administrative, regulatory, and financial hurdles. Other large animal models with more human-like inner ear dimensions are scarce. In this study, we analyzed the inner ears of piglets as a potential representative model for the human inner ear and established a surgical approach for intracochlear drug application and subsequent apical sampling. Further, controlled intracochlear delivery of fluorescein isothiocyanate-dextran (FITC-d) was carried out after the insertion of a novel, clinically applicable CE-marked cochlear catheter through the round window membrane. Two, six, and twenty-four hours after a single injection with this device, the intracochlear FITC-d distribution was determined in sequential perilymph samples. The fluorometrically assessed concentrations two hours after injection were compared to the FITC-d content in control groups, which either had been injected with a simple needle puncture through the round window membrane or the cochlear catheter in combination with a stapes vent hole. Our findings demonstrate not only significantly increased apical FITC-d concentrations when using the cochlear catheter but also higher total concentrations in all perilymph samples. Additionally, the concentration decreased after six and twenty-four hours and showed a more homogenous distribution compared to shorter observation times.